College Calisthenics Teaching Based on Information Technology - Bolong Wang (Applied Bionics and Biomechanics)
Under the background of national fitness, aerobics has become a popular sport. Aerobics has a good fitness effect and is one of the compulsory courses of physical education. But it also puts forward higher requirements for College Aerobics Teaching. The traditional teaching method is no longer applicable. In order to improve the teaching effect of aerobics, this paper puts forward the research of College Aerobics Teaching Method. In this paper, the traditional Aerobics Teaching Methods and the current popular information teaching mode are analyzed in detail. Through the comparison, the traditional aerobics teaching process is too boring to stimulate students’ interest. But after the use of information technology teaching, students’ self-learning ability has been improved. In the study of the effect of traditional teaching mode and information-based teaching mode, this paper makes relevant experimental investigation. The physical fitness of the experimental group was P>0.05. There were significant differences in basic physical qualities such as push-ups, rope skipping, and flexibility between the two groups (P<0.05).The experimental data show that the use of information-based teaching mode is more conducive to students’ accurate grasp of action points, and because of the retrospectivity, students can consolidate knowledge and practice themselves more conveniently. The research of this paper promotes the innovation of traditional education, complements and promotes each other with traditional education, and creates greater learning and exploration space for students, in order to contribute to the construction of aerobics courses in colleges and universities.